Effects of Anthracene Doping Ratio and UV Irradiation Time on Photo-Fries Rearrangement of Polycarbonate - Asrar Saeed et al. (مجلة بغداد للعلوم)
Thin films of pure polycarbonate (PC) with anthracene doping PC films for different doping ratios (10, 20, 30, 40, 50 and 60 ml) were prepared by using a casting method. The influence of anthracene doping ratio on photo-fries rearrangement of polycarbonate was systematic investigated. Furthermore, pure PC and anthracene doping PC films were irradiated via UV light at a wavelength (254 nm) for different periods (5, 240, 288, and 360 hrs). The photo-fries rearrangement occurring in pure PC and anthracene doping PC films were monitored using UV and FTIR spectroscopies. The photo-fries rearrangement leads to scission the carbonate linkage and formation phenylsalicylate and dihydroxybenzophenes. The result of the UV spectrum confirms disappear of polycarbonate peaks, while phenylsalicylate and dihydroxybenzophenone peaks appear at (320 nm) and (360 nm), respectively.  The formation of a dihydroxybiphenyl compound reveals when the UV peak distinguishes at (340 nm). FTIR spectroscopy supported forms of phenylsalicylate and dihydroxybenzophenone compounds which appear in carbonyl region at (1689 cm-1) and (1630 cm-1), respectively. It founds that anthracene accelerates the photo-fries rearrangement of polycarbonate in the anthracene doping PC films because anthracene leads to formation of excited singlet state oxygen (1O2). Singlet oxygen (1O2) leads to the formation of a hydro peroxide, which could decompose and cause to chain scission and formation of a terminal of a carbonyl group. The presence of the carbonyl groups in the polymer makes it photo-labile, also warns that the polymer is vulnerable to deterioration.